Lactobacillus kefiri shows inter-strain variations in the amino acid sequence of the S-layer proteins - Malamud, Mariano (2017)
The S-layer is a proteinaceous envelope constituted by subunits that self-assemble to form a two-dimensional lattice that covers the surface of different species of Bacteria and Archaea, and it could be involved in cell recognition of microbes among other several distinct functions. In this work, both proteomic and genomic approaches were used to gain knowledge about the sequences of the S-layer protein (SLPs) encoding genes expressed by six aggregative and sixteen non-aggregative strains of potentially probiotic Lactobacillus kefiri Peptide mass fingerprint (PMF) analysis confirmed the identity of SLPs extracted from L. kefiri, and based on the homology with phylogenetically related species, primers located outside and inside the SLP-genes were employed to amplify genomic DNA. The O-glycosylation site SASSAS was found in all L. kefiri SLPs. Ten strains were selected for sequencing of the complete genes. The total length of the mature proteins varies from 492 to 576 amino acids, and all SLPs have a calculated pI between 9.37 and 9.60. The N-terminal region is relatively conserved and shows a high percentage of positively charged amino acids. Major differences among strains are found in the C-terminal region. Different groups could be distinguished regarding the mature SLPs and the similarities observed in the PMF spectra. Interestingly, SLPs of the aggregative strains are 100% homologous, although these strains were isolated from different kefir grains. This knowledge provides relevant data for better understanding of the mechanisms involved in SLPs functionality and could contribute to the development of products of biotechnological interest from potentially probiotic bacteria.